Electrical Conductivity of Conducting Polymer Composites based on Conducting Polymer/Natural Cellulose - Sitorus, Berlian; Malino, Mariana B (ELKHA : Jurnal Teknik Elektro, 2021)
Merging each of the best properties of components into a composite design or hybrid architecture opens up opportunities to develop electroconductive materials as conducting polymer composite. This work deals with studying the electrical conductivity of conducting polymer composites made of cellulose extracted from two biomass: empty fruit bunch from oil palm and peat soil. Two kinds of conducting polymers have been used to fabricate the composites, i.e. polyaniline and polypyrrole, which are polymerized from their monomers, aniline and pyrrole. The novelty of this research is the using of biomass as the source of cellulose to produced conducting polymer composites by adding conducting polymer as filler into polymer matrix. We report experimental studies about the influence of monomer addition on the electrical conductivity of composites produced. The conductivity of the material was measured by using the Electrochemical Impedance System method. The experiments were carried out as a four-set experiment, using two different cellulose sources, EFB and peat soil, combined with aniline and pyrrole. The mass ratio variations of the monomer: cellulose are 1, 2, 3, and 4. The conductivities of the composites increased when more aniline or pyrrole was blended with the extracted cellulose from each source, either EFB or peat soil. The conductivity of composite PANI/EFB, which is 3.5 ´10-3 - 1.1 ´10-2 S/cm, is in the semiconductor range that makes the composites useful for many applications.